The Role of MgSO4 in Reducing the Risk of Severe Preeclampsia (PEB) Patients Becoming Eclampsia - Amalia Suryani, Devi Putri (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Preeclampsia is an increase in blood pressure in pregnant women starting at more than 20 weeks of age. Patients with preeclampsia are given MgSO4 as a preventive therapy for eclampsia, where MgSO4 acts as an anticonvulsant that is safe and commonly used in pregnant women. Oktatin's research (2016) found that all patients who used MgSO4 prophylaxis at RSUD dr. Soetomo Surabaya did not experience eclampsia seizures and without symptoms of side effects or drug interactions. In Hariyanti's research (2016) through a retroprespective cohort approach at Fatmawati General Hospital, it was found that the reduction in eclampsia cases in patients with MgSO4 administration was higher than that in patients without MgSO4 administration. Apart from being an anticonvulsant, MgSO4 also plays a role in protecting the fetus